Structure-Specific Ribonucleases for MS-Based Elucidation of Higher-Order RNA Structure - Scalabrin, Matteo (J Am Soc Mass Spectrom, 2014)
Supported by high-throughput sequencing technologies, structure-specific nucleases are experiencing a renaissance as biochemical probes for genome-wide mapping of nucleic acid structure. This report explores the benefits and pitfalls of the application of Mung bean (Mb) and V1 nuclease, which attack specifically single- and double-stranded regions of nucleic acids, as possible structural probes to be employed in combination with MS detection. Both enzymes were found capable of operating in ammonium-based solutions that are preferred for high-resolution analysis by direct infusion electrospray ionization (ESI). Sequence analysis by tandem mass spectrometry (MS/MS) was performed to confirm mapping assignments and to resolve possible ambiguities arising from the concomitant formation of isobaric products with identical base composition and different sequences. The observed products grouped together into ladder-type series that facilitated their assignment to unique regions of the substrate, but revealed also a certain level of uncertainty in identifying the boundaries between paired and unpaired regions. Various experimental factors that are known to stabilize nucleic acid structure, such as higher ionic strength, presence of Mg(II), etc., increased the accuracy of cleavage information, but did not completely eliminate deviations from expected results. These observations suggest extreme caution in interpreting the results afforded by these types of reagents. Regardless of the analytical platform of choice, the results highlighted the need to repeat probing experiments under the most diverse possible conditions to recognize potential artifacts and to increase the level of confidence in the observed structural information.